2016
DOI: 10.1039/c6cy00356g
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM study of the mechanism of reduction of 3-hydroxy-3-methylglutaryl coenzyme A catalyzed by human HMG-CoA reductase

Abstract: Detailing with atomistic resolution the reaction mechanism of human HMG-CoA reductase (HMG-CoA-R) might provide valuable insights for the development of new cholesterol-lowering drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…During recent years, Ramos and coworkers have investigated the reaction mechanisms of a large number of enzymes by employing mostly the B3LYP and M06 functionals with/out dispersion corrections in hybrid QM/MM methods . Here, we focus our attention on some of their works in which several density functionals and/or basis sets were tested, to see how they affect the accuracy of the properties such as activation barriers and reaction energies.…”
Section: Models and Methodologiesmentioning
confidence: 99%
“…During recent years, Ramos and coworkers have investigated the reaction mechanisms of a large number of enzymes by employing mostly the B3LYP and M06 functionals with/out dispersion corrections in hybrid QM/MM methods . Here, we focus our attention on some of their works in which several density functionals and/or basis sets were tested, to see how they affect the accuracy of the properties such as activation barriers and reaction energies.…”
Section: Models and Methodologiesmentioning
confidence: 99%
“…In a more recent study on the catalytic mechanism of human HMG‐CoA reductase, we chose 15 representative structures along a MD simulation to repeat the reaction path. Structures were initially clustered based on the position of residues in the active center.…”
Section: Improving Sampling: Beyond Single‐conformation Qm/mm Methodsmentioning
confidence: 99%
“…The conclusion is consistent with other previous studies, where low-energy barriers were not found in the majority of the explored conformations but still in a very reasonable number of cases. 7,8,49 In analogy to the concept of "static/dynamic/instantaneous disorder" coined in the past for the dispersion in k cat arising from folding uctuations at several timescales, [50][51][52][53] we refer to the phenomenon seen herein as "chemical disorder", with the adjective "instantaneous" due to the nanosecond timescale in which it takes place.…”
Section: Spread Of the Activation Barriers And Chemical Disordermentioning
confidence: 99%